2014
DOI: 10.1016/j.sleep.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Medications associated with restless legs syndrome: a case–control study in the US Renal Data System (USRDS)

Abstract: Objective To determine the association between the usage of four classes of “at risk” medications (antidepressants, neuroleptics, antihistamines, and anti-emetics with dopamine blockade) and restless legs syndrome (RLS) in dialysis patients within the United States Renal Data System (USRDS). Methods This was a case-control design within a national (United States) patient registry of all patients with End Stage Renal Disease (ESRD) in the USRDS anytime during the period of October 1, 2006 and December 31, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 62 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…Patient survival was calculated as the time (in months) from dialysis initiation until transplant, death, or end of study data. Additionally, patients that had been diagnosed with Parkinson’s disease or secondary parkinsonism were excluded to reduce the likelihood of misdiagnosis of RLS due to pre-existing movement disorders [ 27 ]. The comorbidities of interest were identified using ICD-9-CM codes (Additional file 1 : Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Patient survival was calculated as the time (in months) from dialysis initiation until transplant, death, or end of study data. Additionally, patients that had been diagnosed with Parkinson’s disease or secondary parkinsonism were excluded to reduce the likelihood of misdiagnosis of RLS due to pre-existing movement disorders [ 27 ]. The comorbidities of interest were identified using ICD-9-CM codes (Additional file 1 : Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Quetiapine has been found to display a high affinity for the H1 receptor, and several reports have described exacerbation of RLS symptoms on administration of antihistaminic medication [9]. In addition, some investigators have reported that administration of antihistamines, antidepressants, antipsychotics, and antiemetics may increase the risk of RLS in patients with end stage renal disease [10]. However, at the same time, a recent study has revealed the possible involvement of a striatal histamine mechanism in the pathogenesis of iron-deficiency anemia-induced RLS, and that histamine H3R antagonism may be efficacious in its management [11].…”
Section: Histamine and Quetiapine-induced Rlsmentioning
confidence: 99%
“…Dopamine-blocking medications frequently used in end-stage kidney disease, such as antidepressants, neuroleptics, antihistamines and antiemetics, are each associated with doubling of the rate for restless legs syndrome 25. Restless legs syndrome is associated with impaired health-related quality of life, depression and increased mortality among patients with end-stage renal disease 26. Key aspects of management are correction of iron deficiency anaemia and regular exercise.…”
Section: Movement Disorders In the Dialysis Unitmentioning
confidence: 99%